Acceptability and feasibility of using established geosocial and sexual networking mobile applications to promote HIV and STD testing among men who have sex with men - Sun, Christina J. (AIDS Behav, 2015)
This study is the first published multi-app study, of which we are aware, to evaluate both the acceptability and feasibility of providing sexual health information and HIV/STD testing referrals via established geosocial and sexual networking apps for MSM. Data were collected using an online survey and through four apps (A4A Radar, Grindr, Jack’d, and Scruff). Two-thirds (64%) found apps to be an acceptable source for sexual health information. MSM who found apps as acceptable were more likely non-white men, not sure of their current HIV status, and have low HIV testing self-efficacy. One-quarter (26%) of informational chats with the health educator resulted in users requesting and being referred to local HIV/STD testing sites. There were significant differences in the number and types of interactions across apps. Established apps for MSM may be both an acceptable and feasible platform to promote HIV/STD testing. Future research should evaluate interventions that leverage this technology.